Improving the activity of Lycium barbarum polysaccharide on sub-health mice. Issue 6 (10th June 2015) - Zhao, Rui; Cai, Yaping; Shao, Xingyue; Ma, Baoling
<x xml:space="preserve">Abstract</x> Anti-fatigue activity of Lycium barbarum polysaccharide on sub-health mice: LBP-4a exhibited anti-fatigue activity on sub-health mice, and the mechanism was closely correlated with the reduction of lipid peroxidation levels and an increase of antioxidant enzyme activities in skeletal muscle tissue, in addition to the improvement in intracellular calcium homeostasis imbalance of skeletal muscle and an increase in mitochondrial membrane potential.